PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SENI RUPA KELAS VII SMPN 34 PADANG - FATIJAH, Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2019)
The research aimed to find out whether project based learning effects more in the students learning arts outcome rather than conventional learning models which is seen from differences in learning outcomes of students taught using Project Based Learning learning models with student learning outcomes using conventional learning models. The research used quantitative research by having experiment method. The finding showed that students who used project based learning had higher scores rather than who used conventional based learning.Kata kunci: Seni Budaya, Seni Rupa, Model Pembelajaran, Project BasedLearning, Hasil Belajar